Socjologiczne czytanie Biblii. Odnalezione dzieło Bóg Chrystus i Ludzie. Studium socjologiczne ks. Franciszka Mirka (1893-1970) - Kościelniak, Janusz (Poznańskie Studia Teologiczne, 2014)
This article expounds the rediscovered and unpublished manuscript by Father Franciszek Mirek God Christ and the People. A Sociological Study. Father Franciszek Mirek was the first Polish sociologist who was a member of the group of Florian Zaniecki’s students. The recovered manuscript offers an innovative look at the elements of the history of salvation seen through the eyes of a sociologist. The introduction to the paper presents the profile of Father Franciszek Mirek and his most important works. Further parts present the rediscovered manuscript of Fr. Mirek. On its basis the following issues are discussed: the Bible as a source of sociographic data, people as partners in relationship with Christ, the apogee of relations between God and a man in the mystery of the Incarnation of the Son of God and faith as a precondition of human communication with God Christ.